VALES: III. The calibration between the dust continuum and interstellar gas content of star-forming galaxies - Hughes, T.M.; Ibar, E.; Villaneuva, V.; Aravena, M.; Baes, M.; Bourne, N.; Cooray, A.; Davies, L.J.M.; Driver, S.; Dunne, L.; Dye, S.; Eales, S.; et al. (Oxford University Press, 2017)
We present the calibration between the dust continuum luminosity and interstellar gas content obtained from the Valparaiso ALMA Line Emission Survey (VALES) sample of 67 main-sequence star-forming galaxies at 0.02 < z < 0.35. We use CO(1–0) observations from the Atacama Large Millimetre/submillimetre Array to trace the molecular gas mass, MH2, and estimate the rest-frame monochromatic luminosity at 850 µm, Lν850, by extrapolating the dust continuum from MAGPHYS modelling of the far-ultraviolet to submillimetre spectral energy distribution sampled by the Galaxy And Mass Assembly survey. Adopting αCO = 6.5 (K km s−1 pc2)−1, the average ratio of Lν850 /MH2 = (6.4 ± 1.4)× 1019 erg s−1 Hz−1 M−1Θ, in excellent agreement with literature values. We obtain a linear fit of log10 (MH2/MΘ) = (0.92 ± 0.02) log10(Lν850 /erg s−1 Hz−1) − (17.31 ± 0.59). We provide relations between Lν850, MH2 and MISM when combining the VALES and literature samples, and adopting a Galactic αCO value.